2023
DOI: 10.3390/antiox12081491
|View full text |Cite
|
Sign up to set email alerts
|

Advances in Understanding the Role of NRF2 in Liver Pathophysiology and Its Relationship with Hepatic-Specific Cyclooxygenase-2 Expression

Abstract: Oxidative stress and inflammation play an important role in the pathophysiological changes of liver diseases. Nuclear factor erythroid 2-related factor 2 (NRF2) is a transcription factor that positively regulates the basal and inducible expression of a large battery of cytoprotective genes, thus playing a key role in protecting against oxidative damage. Cyclooxygenase-2 (COX-2) is a key enzyme in prostaglandin biosynthesis. Its expression has always been associated with the induction of inflammation, but we ha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 162 publications
0
5
0
Order By: Relevance
“…Subsequently, it dimerizes with sMaf to facilitate the transcription of antioxidant responsive element-containing genes, such as SOD1, SOD2, HO-1, and CAT, to mediate the antioxidant mechanism [41,42]. Additionally, Nrf2 regulates the expression of enzymes involved in GSH production, quinone detoxification, and NADPH synthesis [43]. Moreover, the Nrf2 signaling pathway is involved in inflammation [34,44], cell viability [45], antibacterial activity [36,46], and wound healing [47,48].…”
Section: Discussionmentioning
confidence: 99%
“…Subsequently, it dimerizes with sMaf to facilitate the transcription of antioxidant responsive element-containing genes, such as SOD1, SOD2, HO-1, and CAT, to mediate the antioxidant mechanism [41,42]. Additionally, Nrf2 regulates the expression of enzymes involved in GSH production, quinone detoxification, and NADPH synthesis [43]. Moreover, the Nrf2 signaling pathway is involved in inflammation [34,44], cell viability [45], antibacterial activity [36,46], and wound healing [47,48].…”
Section: Discussionmentioning
confidence: 99%
“…The Nrf2 pathway functions as a cellular defense mechanism, crucial for protecting cells from oxidative stress and inflammation. Studies suggest that silymarin may activate the Nrf2 pathway, serving as a negative regulator of chronic inflammation in LC [ 59 ]. Additionally, considering the central role of HSCs in liver fibrosis [ 60 ], silymarin has been proposed to inhibit their activation [ 24 ].…”
Section: Discussionmentioning
confidence: 99%
“…Abd Allah et al [ 75 ] demonstrated that M. officinalis extract activated Nrf2 in the hippocampus of epileptic rats. It is noteworthy that activation of the Nrf2 pathway enhanced the antioxidant defence system and minimize the production of ROS [ 46 , 76 ]. Furthermore, Wardyn et al [ 77 ] and Vasileva et al [ 78 ] revealed that the activated Nrf2 hampered the inflammatory cascade not only by suppressing NF-κB and pro-inflammatory mediators but also by activating the anti-inflammatory cytokines.…”
Section: Discussionmentioning
confidence: 99%